Curious Oviposition Behavior in Phyllium westwoodii (Phasmatodea: Phylliidae): Preliminary Observations. Issue 1 (25th September 2015) - Arai, Mayuko; Yago, Masaya
Abstract : We report that in a leaf insect, Phyllium westwoodii Wood-Mason (Phasmatodea: Phylliidae), two differing apertures can be used for oviposition, the color of eggs being affected by which aperture is used. Eggs which are forcibly propelled from the internal space within the valvulae of the abdomen are brown, whereas white eggs emerge slowly from the opening between the eighth sternite and the valvulae, and are deposited close to the ventral surface of the female. This unusual oviposition system does not appear to have been previously reported in phasmatids or in other insects.